Flower-like Sc2Mo3O12 nanosheet clusters: Synthesis, thermal expansion and photocatalytic properties. Issue 20 (15th October 2022) - Zhang, Zhiping; Tian, Haodong; Zhang, Chenjun; Zhou, Yuxue; Wang, Wei; Meng, Xiangdong; Liu, Hongfei
Abstract: In this work, Sc2 Mo3 O12 has been synthesized via one-pot hydrothermal reaction. The effects of process conditions on the crystal structure, morphology, photocatalytic activity and negative thermal expansion (NTE) behaviors of flower-like Sc2 Mo3 O12 were systematically investigated. Results indicate that orthorhombic flower-like Sc2 Mo3 O12 assembled by nano-size flaky crystal grains can be synthesized by one-pot hydrothermal reaction at a temperature as low as 120 °C for 2 h. The hydrothermal reaction temperature and time have no obvious effects on the crystal structure and morphology. However, the photocatalytic property of synthesized Sc2 Mo3 O12 is sensitive to the above parameters. The sample synthesized at 200 °C for 2 h shows the best photocatalytic degradation of methyl orange, and the degradation rate is 73.32% in 2 h 1 The coefficient of thermal expansion (CTE) of Sc2 Mo3 O12 is −1.99 × 10 −6 °C −1 in 50–500 °C tested using TMA. The high-temperature XRD analysis reveals that Sc2 Mo3 O12 exhibits anisotropic NTE and the intrinsic CTE is measured to be −2.09 × 10 −6 °C −1 in 25–800 °C.